LSCF-CuO as Promising Cathode for IT SOFC - Ahmad Fuzamy Bin Mohd Abd Fatah; Mohamad Nazri Murat; Noorashrina A. Hamid (Journal of Engineering and Technological Sciences, 2021)
Infiltration of copper oxide towards LSCF was done in order to enhance cathode performance due to superior properties, including high electrical conductivity and high catalytic activity for the oxygen reduction reaction. Samples were synthesized at different temperatures using the sol-gel route. The TGA results showed that LSCF achieved complete perovskite formation when calcined above 600 °C and DTA showed the formation of lattice oxygen at 550 °C. XRD analysis showed no shifted peaks and nano size levels were achieved when samples were calcined at 700 °C and 800 °C. SEM and BET showed similar analysis patterns, where the particle size increased as the calcining temperature was increased. EIS analysis further verified that the polarization resistance of the sample calcined at 700 °C was as small as 0.161 Ω, compared to 1.524 Ω with a calcination temperature of 800 °C. The activation energy of LSCF-CuO was found to be 122.2 kJ/mol, which is much lower than for conventional LSCF.